Evaluasi Perancangan Instalasi Listrik Tenaga di Perusahaan Air Minum - Ilham Rais; Amien Rahardjo; Faiz Husnayain (Website, 2020)
In industrial companies, the electricity system is an important part of production where a good and standard electrical system increases production performance. So that the system is in accordance with the standards, then an electrical system evaluation is carried out. Evaluation is done by simulating power flow and short circuit using ETAP PowerStation 12.6.0 software. The results of the power flow analysis show that the voltage drop on the medium voltage network ranges from 0.04% - 0.05% and low voltage ranges from 0% - 3.36%, which means the system complies with the SPLN 72 1987 and PUIL 2011. Analysis of power flow shows a decrease in the percentage of loading of cables and transformers by 2.34% - 15.74% and in emergency conditions the generator supplies electricity with a percentage of loading of 44.92% when under normal load. Power flow analysis also shows an improvement in power factor from 0.778 lagging to 0.975 lagging. Following Presidential Regulation No. 8 2011, companies do not need to pay additional fees. Short circuit analysis shows there is a breaker equipment whose capacity is below the short circuit current so that it can suffer damage. Based on the analysis of power flow, the electrical design of PT. Aqua Golden Mississippi is in accordance with PLN standards. And based on a short circuit analysis, the problematic breaker equipment must be replaced to reduce damage.